2018
DOI: 10.1590/0037-8682-0109-2017
|View full text |Cite
|
Sign up to set email alerts
|

Hymenoptera stings in Brazil: a neglected health threat in Amazonas State

Abstract: Simple clinical observations and history of injury are critical information for prognostic improvement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 12 publications
(19 reference statements)
0
5
0
1
Order By: Relevance
“…Wasp sting incidents are common worldwide. A large number of published studies have provided information on this public health problem ( Xuan et al, 2010 ; Xie et al, 2013 ; Witharana et al, 2015 ; Costa et al, 2018 ). In this study, we showed elevated serum PCT levels in wasp sting patients.…”
Section: Discussionmentioning
confidence: 99%
“…Wasp sting incidents are common worldwide. A large number of published studies have provided information on this public health problem ( Xuan et al, 2010 ; Xie et al, 2013 ; Witharana et al, 2015 ; Costa et al, 2018 ). In this study, we showed elevated serum PCT levels in wasp sting patients.…”
Section: Discussionmentioning
confidence: 99%
“…Their modified ovipositor, located at the terminal region of the abdomen, functions as a sort of tubular sting that injects venom directly into their prey, enabling a more varied diet (STEEN et al, 2005). These ants have the ability to deliver painful stings that can result in a diverse range of injuries to the victim, from the pain of the sting itself to systemic manifestations such as fever, sweating, tremors, nausea, vomiting, lymphadenopathy, and cardiac arrhythmias (HADDAD et al, 1996;COSTA et al, 2018;SHARMA e UPADHYAY et al, 2021;AGARWAL et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Hymenopteran venoms, inoculated during stings by ants, bees, and wasps, for example, are the most frequent cause of an IgE-mediated systemic hypersensitivity reaction in adults, which is a key process in drastic manifestations of anaphylaxis. 1,2 The clinical presentation of wasp envenomation is related to the components of the venom that contain phospholipase A1, hyaluronidase, antigen 5, melittin, amines such as histamine and serotonin and kinins, apamin and acetylcholine. 3 Acute renal failure, nephrotic syndrome, renal tubular acidosis, myocarditis, myocardial infarction, arrhythmias, centrilobular necrosis, pericolangitis, stroke, acute encephalopathy, hemolysis, disseminated intravascular coagulation, thrombocytopenia, and vasculitis are the main manifestations of a severe envenomation.…”
Section: Introductionmentioning
confidence: 99%